IMPROVING MATHEMATICAL CONNECTION ABILITY OF VOCATIONAL HIGH SCHOOL STUDENTS BY USING THE PROBLEM BASED LEARNING - Sulaeman, Ariyadi; yusniawati, Yayu; Rohaeti, Euis Eti (IAPM UNSUR (Ikatan Alumni Pendidikan Matematika Universitas Suryakancana))
this study aims to determine the achievement of students mathematical connection ability whose learning to use problem based learning